INNOVATIVE EDUCATION MANAGEMENT STRATEGIES TO INCREASE PARENTAL INOLVEMENT - Kulsum, Ummi; Jazilurrahman, Jazilurrahman; Hambali, Hambali; Imami, Agus Sulthoni; BZ, Zakiyah (PROCEEDING OF INTERNATIONAL CONFERENCE ON EDUCATION, SOCIETY AND HUMANITY, 2024)
This research aims to identify and analyze innovative educational management strategies that can increase parental involvement at Sirojul Ummah Prasi Gading Senior High School (SMA). Data analysis using data collection methods carried out observations, interviews and documentation analysis to gain an in-depth understanding of the challenges faced in parental involvement and develop innovative strategies that can be implemented. This research uses qualitative analysis research methods. With the research location at Sirojul Ummah Prasi Gading High School (SMA). In this case, collaboration between schools and parents is the main key. The research identified several innovative strategies, such as using digital platforms for real-time communication, involving parents in decision making through regular meetings, and organizing joint activities that involve parents in the educational process.